1998
DOI: 10.1007/s004020050331
|View full text |Cite
|
Sign up to set email alerts
|

Changes of biochemical markers during fracture healing

Abstract: The aim of this study was to evaluate the changes of biochemical markers during fracture healing in patients with osteoporosis. The study included 26 patients; 9 underwent hip hemiarthroplasty (mean age +/- SD: 71.0 +/- 10.2 years, group EN) for femoral neck fractures. 7 underwent osteosynthesis (75.3 +/- 8.2 years, group OS) for trochanteric fractures, and 10 subjects had spinal compression fractures (68.2 +/- 12.0 years, group CO). No operative procedures were performed in group CO. Urinary pyridinoline (Pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 17 publications
5
43
2
Order By: Relevance
“…All of these serum markers increased or decreased after different skeletal bone fractures and fluctuated during fracture healing in agreement with the literature data (14,(24)(25)(26). For example, OC elevated at 24 weeks after fracture of the tibial shaft and rose at 1 week after distal radial fracture.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…All of these serum markers increased or decreased after different skeletal bone fractures and fluctuated during fracture healing in agreement with the literature data (14,(24)(25)(26). For example, OC elevated at 24 weeks after fracture of the tibial shaft and rose at 1 week after distal radial fracture.…”
Section: Discussionsupporting
confidence: 90%
“…PYD-DPYD peaks 1 to 8 weeks after proximal femoral fracture, and PYD peaks 1 to 4 weeks after fracture of the tibial shaft. PYD is a less specific marker of bone resorption than DPYD since it is abundant in all connective tissues; however, DPYD is distributed generally in bone and dentin, and 90% of the bone matrix consists of type I collagen (14,26). In the present study, no significant changes were observed for the markers of bone formation and resorption analyzed between the groups.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…started to increase 2 weeks after fracture, and values at 48 weeks were still higher than the initial values. This pattern of changes in bone resorption and formation markers was mostly consistent in the case of hip fracture [21].…”
Section: Discussionsupporting
confidence: 72%
“…Bone resorption and formation markers change dramatically after fracture of long bones because of the fracture healing and repair process [2,[12][13][14]21]. Bone resorption markers increased soon after a fracture event and bone formation markers increased gradually thereafter.…”
Section: Introductionmentioning
confidence: 99%